FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN SIKAP DAN ORIENTASI PEMILIH TERHADAP CALON LEGISLATIF PADA PEMILU 2009 DI DAERAH PEMILIHAN TAWANG-CIHIDEUNG KOTA TASIKMALAYA - Edi Kusmayadi; Akhmad Satori; Mohammad Ali Andrias; Taufik Nurohman; Chandra Budi LS (Jurnal Ilmu Politik dan Pemerintahan, 2011)
The Elements who Influence Orientasion and Attitudes Voters Concerning Legislative Candidates in General Election 2009 at Election District Tawang-Cihideung Tasikmalaya City. Voters behavior in general election 2009 very different with voters behavior in general election 2004. Voters confronted with legislative candidates who have to be votes and so do the political party who take the legislative candidates, so many voters who had multiple diverse orientation and attitude. The most attitude who have affected orientasion and attitude voters to legislative candidates.This research be done at election district 1 Cihideung-Tawang, in this district there are 116 legislative candidates from 25 political party who there in election district 1, they are joining in legislative election 2009. living hood, primordialism, voters loyality, job and propechy, it becomes the most influence elements of orientation and attitude change of the voters.